Family history of type 2 diabetes and characteristics of children with newly diagnosed type 1 diabetes - Parkkola Anna; Turtinen Maaret; Härkonen Taina; Ilonen Jorma; Knip Mikael; Finnish Pediatric Diabetes Register (Springer, 2022)
Aims/hypothesis
Shared aetiopathogenetic factors have been proposed in type 1 diabetes and type 2 diabetes and both diseases have been shown to cluster in families. Characteristics related to type 2 diabetes have been described in patients with type 1 diabetes with a positive family history of type 2 diabetes. We wanted to characterise the family history of type 2 diabetes and its possible effects on the phenotype and genotype of type 1 diabetes in affected children at diagnosis.
Methods
A total of 4993 children under the age of 15 years with newly diagnosed type 1 diabetes from the Finnish Pediatric Diabetes Register were recruited (56.6% boys, median age of 8.2 years) for a cross-sectional, observational, population-based investigation. The family history of diabetes at diagnosis was determined by a structured questionnaire, and markers of metabolic derangement, autoantibodies and HLA class II genetics at diagnosis were analysed.
Results
Two per cent of the children had an immediate family member and 36% had grandparents with type 2 diabetes. Fathers and grandfathers were affected by type 2 diabetes more often than mothers and grandmothers. The children with a positive family history for type 2 diabetes were older at the diagnosis of type 1 diabetes (p < 0.001), had higher BMI-for-age (p = 0.01) and more often tested negative for all diabetes-related autoantibodies (p = 0.02).
Conclusions/interpretation
Features associated with type 2 diabetes, such as higher body weight, older age at diagnosis and autoantibody negativity, are more frequently already present at the diagnosis of type 1 diabetes in children with a positive family history of type 2 diabetes.